Empowering Post-Stroke Patients to Improve Self-Care and Prevent Recurrent Stroke Using Stroke Empowerment Education - Prasetyowati, Christina Dewi; Firmanda, Giovanni Iga (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: Stroke can lead to varying outcomes, ranging from recovery with disability, death, to surviving with recurrent strokes. Post-stroke patients require special attention to improve self-care behaviors. Stroke empowerment education is an educational approach given to stroke patients with an empowerment-focused approach centered on the patient. This study aimed to determine the effect of stroke empowerment education on the self-care of post-stroke patients as an effort to prevent recurrent strokes at RSUD Gambiran Kota Kediri. Methods: The research design used was a Quasi-Experiment with a pre-post test design with a control group. Sampling was done using accidental sampling technique, resulting in 98 respondents. Data collection on self-care was conducted using the modified version of The Subjective Self-Care Performance Scale questionnaire. Results: The results of the Wilcoxon Signed Ranks Test showed significant improvement (p = 0.000) in self-care among post-stroke patients after Stroke Empowerment Education. Conclusion: This study concluded that there was an effect of stroke empowerment education on improving self-care among post-stroke patients as an effort to prevent recurrent strokes at RSUD Gambiran Kota Kediri. As a recommendation, the results of this study can be continued as an intervention in hospitals to enhance services for post-stroke patients to improve self-care as an effort to prevent recurrent strokes.